Desarrollo de un sitio web auto-administrado para la fundación cristo vive en mi - Gilbert Zhune, Enrique Arturo (2011)
The foundation " Cristo Vive en Mí " located in the citadel La Fragata south of Guayaquil, working with vulnerable social sectors by providing financial assistance, psychological and spiritual child nutrition, parenting, juvenile delinquency and drug addiction. The Foundation was created in 2006 by a group of Christian missionaries, was not released until November 2010 because it lacked a communications channel that allows events to present performing and reporting on social services provided; to encourage more people to participate and cooperate with it. For the development and implementation of this project, a study needs to crystallize the idea of developing a communication channel low operating costs, such as transmitting information, a means of communication with partners and beneficiaries, maintain a record members and is open to the needs of beneficiaries, as a better alternative and objective of this project is therefore focused on developing a self-administered Web site, which was implemented successfully.